Effects of Process Cutting Parameters on the Ti-6Al-4V Turning with Monolithic Driven Rotary Tool - Joch, Richard; Šajgalík, Michal; Czán, Andrej; Holubják, Jozef; Cedzo, Miroslav; Čep, Robert (Materials, 2022)
Machining with rotating tools appears to be an efficient method that employs a non-standard kinematic turning scheme. It is used in the machining of materials that we classify in the category of difficult to machine. The titanium alloy Ti-6Al-4V, which is widely used in industry and transportation, is an example of such material. Rotary tool machining of titanium alloys has not been the subject of many studies. Additionally, if researchers were dissatisfied with their findings, the reason may not be the kinematic machining scheme itself but rather the tool design and the choice of cutting parameters. When tools are constructed of several components, inaccuracies in production and assembly can arise, resulting in deviations in the cutting part area. A monolithic driven rotary tool eliminates these factors. In the machining process, however, it may react differently from multi-component tools. The presented work focuses on the research of the technology for machining titanium alloy Ti-6Al-4V using a monolithic driven rotary tool. The primary goal is to gather data on the impact of cutting parameters on the machining process. The cutting force and the consequent integrity of the workpiece surface are used to monitor the process. The speed of workpiece rotation has the greatest impact on the process; as it increases, the cutting force increases, as do the values of the surface roughness. In the experiment, lower surface roughness values were attained by increasing the feed parameter and the depth of cut. This may predetermine the inclusion of a kinematic scheme in highly productive technologies.